Entrepreneurial Fuel for Success: The Influence of Opportunity and Skills on Student Entrepreneurial Motivation - Shandy Aditya; Meta Bara Berutu; Zidane Ramadhan (LPPM Universitas Negeri Jakarta, 2024)
This research aims to analyze the influence of skills and opportunities on entrepreneurial motivation among Indonesian students. Using quantitative methods, this research collected data from 314 students who were randomly selected through a digital questionnaire. Regression analysis shows that both skills and opportunities have a significant positive influence on entrepreneurial motivation, with skills having a more dominant impact. These results indicate that developing entrepreneurial skills through education or related programs can increase students' entrepreneurial motivation. It is hoped that these findings can contribute to the entrepreneurship literature in the Indonesian context and help develop more effective entrepreneurship programs in higher education.